DETERMINING BUSINESS CONSTRAINTS AMONG INDONESIAN WOMAN ENTREPRENEURS: STUDY FROM LOCAL MSME COMMUNITY - Setiawati, Cut Irna; Zulfaa Putri Nabiilah (Dinasti International Journal of Digital Business Management, 2020)
The rapid growth in the number of women entrepreneurs, isn’t equal to the growth of their businesses which are relatively slower. Same thing that occur to Benua Citra Niaga MSME community (BCNc), which have 66,67% women members. Only 30% of women entrepreneurs in BCNc who showed business growth, while other 70% are stagnant. Thus, this study aims to find out factors that constraining the business success of women entrepreneurs in BCNc. This study used a quantitative method. Factor analysis used for analyzing data. The findings of this study indicate that there are 9 dominant factors: lack of networks to financial institution, underestimated in the business and family environment, lack of business education and experience, unfavorable business regulation, unsupportive economic and political environment, assets price and taxes problem, work-life imbalance conflict, limited training and community access, and hiring unqualified employee. The most dominant factor is lack of networks to financial institution.